A Support System for Sensor and Information Fusion System Design. (2016) - Fritze, Alexander; Mönks, Uwe; Lohweg, Volker
Abstract: The complexity of industrial applications has constantly increased over the last decades. New paradigms arise in the context of the fourth industrial revolution by bringing together mechatronic systems and information technologies. Tasks like information processing, extensive networking, or system monitoring using sensor and information fusion systems are incorporated with the aim to design applications that are capable for self-configuration, -diagnosis, and -optimisation. This contribution focuses on the design of sensor and information fusion systems. A methodology for the design process of such systems is proposed that serves as tool for auto-configuration to facilitate self-diagnosis and -optimisation.